Physical Activity and Cognitive Function in Middle and Late Adulthood ‒ Results of a Preliminary Study - Gawron, Natalia; Zębrowski, Aleksander; Hintze, Beata (Przegląd Psychologiczny, 2024)
Objective: The aim of the study was to characterise the physical activity (PA) of middle-aged and older adults and to determine whether the amount of PA was related to their level of cognitive function. Methods: This was a cross-sectional study of 52 women and 30 men aged 50‒80 years. Subtests of the Wechsler Intelligence Scales for Adults Revised Version ‒ Renormalisation WAIS-R(PL) were used to assess cognitive function: Digit span, Block design and Digit symbol, as well as the Colour Trails Test (CTT) and the Link’s cube task. Physical activity was measured using the International Physical Activity Questionnaire-Long Version (IPAQ-LF) and a pedometer worn by the volunteers for one week. Associations between cognitive function and PA were estimated using non-parametric correlations. In addition, cognitive function and PA were compared in healthy participants, participants with one chronic condition, and participants with two or more conditions. Results: Walking, as measured by a pedometer, was at an average level in the study participants, and PA, as reported on the IPAQ-LF questionnaire, was very high. There were few associations between PA and cognitive performance. Moderate and vigorous levels of PA reported on the IPAQ-LF were correlated with more accurate performance on the Block design and Link’s cube tasks. Higher levels of leisure time PA reported on the IPAQ-LF were correlated with better performance on the CTT. More PA at work was correlated with higher performance on most tasks. Activity measured by number of steps did not correlate with cognitive function. More steps correlated with less time spent inactive on the IPAQ-LF. In addition, healthier participants performed better on cognitive tasks and took more steps than those with chronic conditions. Conclusion: The research has contributed to the understanding of the relationship between real-life PA and cognitive function in middle-aged and older adults, and has provided important insights into PA in these individuals.